State-minority contestations in post-colonial Sri Lanka / Mansoor Mohamed Fazil - Mansoor , Mohamed Fazil (2018)
Sri Lanka is known worldwide for the civil war that has ravaged this country over the last three decades. The Liberation Tigers of Tamil Eelam (LTTE) was organised to be the leading Tamil militant social force and to wage war against the government to form a separate state in the northern and eastern regions of Sri Lanka. After the government ended both the separatist struggle of the LTTE and the civil war in May 2009, the protracted and destructive 30-year war should have created an opportunity for both state and society to learn the lessons of the long war. These lessons should have enabled them to reconstitute the state as an inclusive institution, one that minorities could also participate in to ensure just and equitable development for all Sri Lankans. This research aims to answer the following key questions: What are the factors that contributed to the failure of the strong minority social force that was formed to reconstitute and create a new, inclusive state? What are the key lessons for the state and the Tamil minority group that can be derived from the civil war that ended in 2009? Why has the state not responded with inclusive policies to prevent another major contestation? This study uses a qualitative research method that involves critical categories of analysis. The state, society, and international categories were selected for assessment through a purposive sampling of information-rich cases. Migdal’s theory of state-in-society was applied because it provides an effective conceptual framework to analyse and explain the data. The results indicate that the unitary state structure and discriminatory policies contributed to the formation of a minority militant social force. In the context of Sri Lanka, this social force challenged the state’s sovereignty and control of substantial land areas, occupied these minority-dominant territories and introduced security, administrative, and financial systems to support these people. The strong leadership that assumed the presidency of the state, the strengthening of security forces, and subsequent implementation of sophisticated security strategies, as well as factions among elites of the social force and the global war on terrorism, are major factors that contributed to the defeat of the LTTE in 2009. This defeat has appreciably weakened the Tamil minority. The state-in-society approach argues that a weak society will encounter difficulty transforming and reconstituting a strong state, which is a pivotal question in the present context of Sri Lanka. While both state and society learnt lessons from the protracted and destructive war about the need to avoid future contestations, lack of elite consensus among members of the majority ethnic group, influence of radical movements, existence of a strong but unstable state, and lack of unity among minority sociopolitical movements are factors that hindered the introduction of inclusive policies. Interestingly, this study also reveals that contestations between different social forces within society, within the state, and between the state and society in Sri Lanka still prevail, hampering the promulgation of inclusive policies. This study concludes that inclusive policies are imperative to end state minority contestations in Sri Lanka.